An Overview and Informal Key of the Ferns of Florida - Douglas G. Scofield; Ginger M. Allen; Martin B. Main (EDIS)
Florida's temperate to subtropical climate and abundant moisture create excellent growing conditions for ferns. Tropical storms and winds have transported fern spores to Florida from Caribbean islands and resulted in a high diversity of species. Consequently, Florida has more species of ferns than any state except Hawaii. There are an estimated 123 native fern and fern-like species, and at least 21 exotic and hybrid (crossbreeding of two species) species of ferns found in Florida.  This document is Circular 1471, one of a series of the Wildlife Ecology and Conservation Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2005.